2014
DOI: 10.3109/1354750x.2014.896946
|View full text |Cite
|
Sign up to set email alerts
|

Fibrosis markers and CRIM1 increase in chronic heart failure of increasing severity

Abstract: Background: Fibrosis suppressors/activators in chronic heart failure (CHF) is a topic of investigation. Aim: To quantify serum levels of fibrosis regulators in CHF. Methods: ELISA tests were used to quantify fibrosis regulators, procollagen type-(PIP)I, (PIP)III, collagen-I, III, BMP1,2,3,7, SDF1a, CXCR4, fibulin 1,2,3, BMPER, CRIM1 and BAMBI in 66 CHF (NYHA class I, n ¼ 9; II, n ¼ 34; III n ¼ 23), and in 14 controls. Results: In CHF, TGFbR2, PIPIII, SDF1a and CRIM1 were increased. PIPIII correlated with CRIM1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
(50 reference statements)
1
2
0
Order By: Relevance
“…Similar to prior studies in patients with heart failure overall [31][32][33][34] , higher serum levels of IL6 or CRIM1 were associated with more severe forms of inflammatory cardiomyopathy in our study. Importantly, it had been shown previously that in IL6 deficient mice, prevalence and severity of myocarditis were reduced in the absence of IL6 31 .…”
Section: Discussionsupporting
confidence: 90%
“…Similar to prior studies in patients with heart failure overall [31][32][33][34] , higher serum levels of IL6 or CRIM1 were associated with more severe forms of inflammatory cardiomyopathy in our study. Importantly, it had been shown previously that in IL6 deficient mice, prevalence and severity of myocarditis were reduced in the absence of IL6 31 .…”
Section: Discussionsupporting
confidence: 90%
“…One study showed that statins decrease circulating fibrosis markers in patients with HF. 12 However, several factors can affect circulating fibrosis markers in patients with HF, including HF severity, 35 renal function, 36 and cardiac function. 17 Therefore, lower levels of circulating fibrosis markers in HF are hard to interpret.…”
Section: Discussionmentioning
confidence: 99%
“… 22 , 23 , 24 Interestingly, CRIM1 was documented to be expressed in coronary vascular smooth muscle cells and coronary endothelial cells during cardiac development 24 and serum levels of CRIM1 were reported to positively correlate with the severity of left ventricular failure in human. 25 SPON1 is a secreted and extracellular matrix‐attached protein of the thrombospondin family with obscure functions. Early work on this protein indicated that it stimulates vascular smooth muscle cell proliferation 26 and inhibits angiogenesis, 27 suggesting that increased plasma levels in patients with PAH may contribute to RV ischemia.…”
Section: Discussionmentioning
confidence: 99%